Evaluation of the effectiveness of electroconvulsive therapy in the treatment of psychosis in a patient with epilepsy. Clinical case - T. V. Dokukina; F. P. Khlebokazov; I. I. Khvostova; N. N. Misyuk; K. A. Bondar; P. P. Korolevich; E. L. Slobina; I. S. Glavinskiy (Эпилепсия и пароксизмальные состояния)
The results of successful treatment of schizophrenic psychosis with persistent catatonic symptoms, refusal to eat in a patient with epilepsy are presented. In view of the progressive course of the disease, the lack of dynamics from the ongoing drug treatment, the method of electroconvulsive therapy was applied. Epileptic seizures and visual signs of brain epileptization were absent with the development of psychosis. As a result of the course of electroconvulsive therapy (9 procedures), the patient's clinical condition improved significantly. This observation illustrates the possibility of using electroconvulsive therapy in combination with antipsychotics and antiepileptic drugs as an alternative method for treating drug-resistant epilepsy.